DISCUSSION SUR L'AGE MURGABIEN OU MIDIEN DES SERIES PERMIENNES DU JEBEL TEBAGA (SUD DE LA TUNISIE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
A biostratigraphical analysis of Jebel Tebaga (Tunisia) is given. The Permian is divided in two zones: Afghanella zone of Middle-Upper Murgabian age; and Neoschwagerina, Yabeina and Dunbarula zone of Upper Murgabian- Lower Midian age, himself divided in a lower subzone with Dunbarula nana and an upper subzone wirh Dunbarula mathieui and Codonofusiella.
Keywords: Permian; Biostratigraphy; Foraminifera; Chronostatigraphy; Tethys.